Current Trends and Opportunities for Business Transformation in Enterprises in The Global Economy - Prabhu, Juandri (International Journal of Economics and Business Management, 2024)
Going forward, 2022 will be the year that digitalization efforts pay off, which is ultimately good news. In 2022, digitalization efforts will continue to expand rapidly in every company. The last few years of business have changed the way we work and the structure of companies. In the search for greater efficiency, economies of scale and lower costs, companies have stuck to trends such as outsourcing, offshoring, mergers and acquisitions, but rapid technological developments have changed the way information is shared and disseminated, as well as controlling business cycles andtransactions. Offshoring, mergers, acquisitions and large-scale IT projects may have different objectives and require different skills, but for the most part they are examples of business change. In any type of project, leaders must set clear goals, ensure that they are understood by everyone in the organization, and carefully focus the implementation phase to ensure that the goals are met. This means that every project involves managing change at scale, which is a complex and challenging task in today's highly distributed, global organizations. Based on a review and systematic research, we explore the trends that drive business change and explore the challenges and opportunities presented by this critical aspect of modern business